Laparoscopic versus open appendicectomy-a comparative study of clinical outcomes in an institutional centre - Fatma, Noorin; Kumar, Binod; Jha, A. K.; Thakur, Indra Shekhar (International Journal of Research in Medical Sciences, 2023)
Background: Appendicectomy remains to be one of the most common procedures performed by the general surgeon. Laparoscopic appendicectomy is likely to have less postoperative pain, less use of analgesics, early discharge, decreased wound infection, better cosmetics and also diagnostic and early return to routine work. Method: This is a comparative study of 50 cases of appendicitis divided equally into two groups 25 in open and 25 in the laparoscopic which were randomly selected and operated in the department of general surgery at PMCH, Patna. Results: In present study pain score was 2.97±0.7 for open group as compared to 1.56±0.7 in lap group (p<0.05) because of longer incision stretch of muscles and wound infection. Post operative complications like vomiting was lower in laparoscopic group with 12% as compared with 40% in open group (p<0.05) and ileus was lower in lap group with 27±4.6 and for open group 31±5.4 with p<0.05 which were significant. There is significant reduction in incidence of post operative wound infection in lap group 0% as compared to open group 32% (p<0.05). Duration of postoperative hospital stay was significantly low for lap group 2±0.78 as compared to open group 8±0.89. The return to normal activity was low for lap group 14±2.11 days as compared to open group 21.7±3.7days. Duration of surgery for open appendicectomy was 48±19 mins and for lap appendicectomy was 46±15 mins. Conclusions: Overall laparoscopic appendicectomy is better than open appendectomy in selected patients with acute or recurrent appendicitis.